Persepsi Kelompok Wanita Tani Berkah MBR Bogor Sebagai Pelaku Urban Farming Terhadap Penerapan Digital Marketing - Afifah, Ulil Azmi Nurlaili; Manalu, Doni Sahat Tua; Rusmiyati, Henny; Hapsari, Dhika Prita; Marithasari, Harries; Fauzan, Farhan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Berkah MBR Women's Farmers Group operates in the agribusiness sector and was founded in 2020. Urban farming development activities (cultivation, processing and marketing) by utilizing existing land and resources are carried out on a massive scale by groups such as the MBR Berkah Farmers Group. The research was carried out on urban farming land belonging to the Berkah MBR Women's Farming Group and residents in Katulampa Village, East Bogor. The analytical methods used are descriptive statistics and inferential statistics. Descriptive statistics are used to describe the perceptions of the Women Farmers Group and residents regarding the use of Digital Marketing. The type of data used is primary data obtained through a questionnaire using a questionnaire instrument implemented via Google Form. Based on research results, the Berkah MBR Women's Farming Group has the perception that conventional marketing of urban farming products needs to be supported by digital marketing. KWT MBR also generally believes that digital marketing techniques using WhatsApp, YouTube, Facebook, TikTok and Instagram are important to learn and apply because they can generate large profits.